Medial students' attitudes about female rape victims - Best, Connie L. (Journal of interpersonal violence, 1992)
The goal of the present investigation was to examine the extent to which assault and participant characteristics influence medical students' attitudes toward rape and nonsexual assault victims. First-and third-year medical students read narratives of three types of patients-a stereotypical rape victim, a victim of a robbery, and a nonstereotypical rape victim-and responded to an attitude questionnaire in reference to the victims in the narratives. The results of a series of ANOVAs showed that females had more favorable attitudes toward victims than males did and that medical students had more victim-blaming attitudes about a nonstereotypical rape victim than about either a stereotypical rape victim or a nonsexual assault victim. The implications of these findings are discussed with respect to service delivery for rape victims and medical school curricula